Development of Maraging Steel with Retained Austenite in Martensite Matrix. (2015) - El-Fawkhry, M.K.; Eissa, M.; Fathy, A.; Mattar, T.
Abstract: This research considers as a trial for solving the debate on the role of retained austenite in improving the mechanical properties and design's requirements of maraging steel. Four compositions of Maraging steel have been selected in this study, and the role of retained austenite in improving the mechanical properties of maraging steel was evaluated. The results showed a significant effect of retained austenite fraction on the mechanical properties of the developed steel in particular ductility, tensile strength, and strain hardening property. Therefore, the retained austenite content has a positive effect in the term of material designing.